Utilization of waste construction materials in concrete - Manoj Yadav.B, Maheswararao.R, V.Srinivasa Reddy, Ashok Kumar.T, Kamalakar.V, Irfana Barveen R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The concrete manufacturing as well as development enterprises are liable for a specific piece of ozone harming substance emanations, created in the clinkering period of concrete creation, which add to an Earth-wide temperature boost. The thing is serious to reuse these materials and reject them. The article provides a general overview of the literature on how cell cement, concrete, and sand-lime results have altered how traditional building materials are organized. My own investigation and list of questions about them are included in the publication. The review's objective was to compare newly developed materials to their more established counterparts in order to ascertain how the addition of chemicals influenced the upper limits of physical and mechanical capabilities as well as the microstructure. Compressive strength, water intake, mass thickness, and development of primary material have all been exposed to the examination's results. Tables and graphs are used to present the findings